Correlations between body composition and aerobic fitness in elite female youth water polo players - Zamodics, M.; Babity, M.; Schay, G.; Leel-Ossy, T.; Bucsko-Varga, A.; Kulcsar, P.; Benko, R.; Boroncsok, D.; Fabian, A.; Ujvari, A.; Ladanyi, Z.; Balla, D.; et al. (Sports, 2025)
Body composition and cardiopulmonary exercise testing (CPET) are vital for optimizing sports performance, but the correlations between them are still underexplored. Our study aimed to investigate the relationships between body composition and specific CPET variables describing physical fitness in young athletes, also adjusting for age and height, in a less-studied, female population. Seventy players participated in our study (age: 16.10 ± 1.63 y). After determining body composition using dual-energy X-ray absorptiometry, we conducted treadmill-based maximal-intensity CPET. Data were analyzed in R using multivariate linear regression, accounting for age and height as confounders. Lean body mass (LBM), body fat mass (BFM), and bone mineral content (BMC) showed no effect on resting, maximum, or recovery heart rates and no correlation with resting or maximal lactate values. LBM positively correlated with maximum ventilation (VE-max) (Est: 1.3 × 10-3; SE: 6.1 × 10-4; p < 0.05) and maximum absolute oxygen consumption (VO2abs-max) (Est: 7.710-5; SE: 6.9 × 10-6; p < 0.001)—with age as an influencing factor for VE-max and height as an influencing factor for VO2abs-max. Conversely, BFM showed a negative correlation with maximum relative oxygen consumption (VO2rel-max) (Est: -4.8 × 10-4; SE: 1.2 × 10-4; p < 0.001). Moreover, BFM and BMC were also negatively correlated with maximal exercise duration (Est: -2.2 × 10-4; SE: 8.0 × 10-5; p < 0.01; Est: -3.2 × 10-3; SE: 1.4 × 10-3; p < 0.05) with height as an influencing factor. Our findings indicate complex correlations between body composition and CPET parameters, providing important information for the analysis of individual ergospirometric data. Our results draw attention to the fact that body composition is more precise than weight and height in the evaluation of athletes` physical fitness.